Composición florística y estructura del bosque secundario de la finca Don Villa, en el Cantón Quevedo, Provincia de Los Ríos. - Zambrano Basurto, María Magdalena (2015)
This research was conducted on the property of Lcdo. Marco Villarroel located in the canton La Pepita sector Quevedo, Los Rios province between UTM coordinates 668148 and 9886700. The aim of this study was to: analyze the floristic composition and structure of secondary forest farm Don Villa. This study was conducted in a patch of forest, in which 10 sampling units 4002 (20 mx 20 m), randomly distributed in three blocks (4 plots in Block 1, 3 in block 2 and 3 are established in block 3). In each plot the trees with DBH ≥ 7.5 cm were recorded, height and common name of the species was recorded. A total of 158 trees, covered by 18 families, 29 genera and 31 species were found. The most abundant species were: A. excelsum, E. poeppigiana, S. parahybum, Z. C. tachuelo and C elastica. The Shannon index value indicates that the forest contains a median diversity. The species with the highest Importance Value Index (IVI) were: A. excelsum, E. poeppigiana, S. parahybum, C elastica, and T. cumingiana. Most trees (65) are in the range of 10 to 20 cm of DAP. With respect to height 85 species found in the middle layer. The diversity of the studied forest is lower than the results reported by other studies for secondary forest in the tropics. The results suggest actions to implement the conservation and enrichment with native species in the area